INVENTARISASI GULMA PADA TANAMAN KARET (Hevea brasiliensis) DI BALAI PENGAWASAN DAN SERTIFIKASI BENIH PERKEBUNAN - Dewi Amelia Widiyastuti (Agrisains: Jurnal Budidaya Tanaman Perkebunan Politeknik Hasnur, 2020)
The purpose of this research is to know the botanical and morphology of any weeds that attack the rubber plant and weed control doneAt Balai Pengawasan And Sertifikasi Benih Perkebunan. The method used is descriptive method with data collection techniques through observation, interview and documentation. Based on the observation it can be seen that the weeds that attack the rubber plant in the Plantation Monitoring and Certification Seed in morphology are weeds, including the broad-leaved plant species and the puzzles such as jukut pahit (Axonopus compressus), Ara Sungsang (Asystasia ganggetica L), Senduduk (Melastoma malabratichum), Babadotan (Ageratum conyzoides), Imperata cylindrica, Putri Malu (Mimosa pudica), Meniran (Phyllanthus niruri), Jukut Pendul (Kyllinga brevifolia). By way of control is done spraying using Gramoxone contact herbicide with a dose of ± 28 ml per 1 tank hands sprayer solo contents of 14 liters of  water for to the field of weeds attacked rubber plantation. At the  Plantation Regulatory Monitoring and Certification Center for 0.5 hectares of land required 252 ml herbicide. Anddoneint spraying when the weather is sunny.